Effects of lung recruitment maneuver using mechanical ventilator in preterm infant microcirculation: a clinical trial - Iskandar, Adhi Teguh Perma; Djer, Mulyadi Muhammad; Supriyatno, Bambang; Kaban, Risma Kerina; Kautsar, Ahmad; Rahmadhany, Anisa; Sutjipto, Fiolita Indranita; Suhendro; Advani, Najib; Santoso, Dewi Irawati Soeria; Prihartono, Joedo; Yuniati, Tetty (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Preterm infants often require continuous positive airway pressure due to immature respiratory tracts. Bronchopulmonary dysplasia (BPD) manifests as prolonged oxygen dependence until 28 days of age and is classified into mild, moderate, or severe forms. The lung recruitment maneuver (LRM) aims to reopen collapsed alveoli, enhancing oxygenation during mechanical ventilation using the assist control volume guarantee mode (MV-AC/VG). This study aimed to evaluate the impact of LRM on alveolar and endothelial injuries, neonatal microcirculation, and its relation to BPD reduction or mortality in preterm infants. METHODS This study was conducted from March 2021 to April 2022 at Cipto Mangunkusumo and Bunda Menteng Hospitals, Jakarta. The participants are <32 weeks infants with severe respiratory distress syndrome requiring MV-AC/VG, divided into LRM and control groups (n = 55 each). The alveolar injury was assessed using plasma surfactant protein-D (SP-D), endothelial injury by flow cytometry for endothelial microparticles (CD-31⁺/CD-42-), and neonatal microcirculation via transcutaneous-artery CO2 gap (TcPCO₂-PaCO₂) and transcutaneous O2 index (TcPO₂/PaO₂) measurements at 1 and 72 hours post-ventilation. RESULTS LRM did not negatively affect preterm infants (24–32 weeks) undergoing invasive mechanical ventilation. At 72 hours, no significant differences were observed in alveolar (SP-D) and endothelial injury (CD-31+/CD-42-), nor in BPD reduction or mortality by 36 weeks. CONCLUSIONS LRM is a beneficial intervention for enhancing respiratory support and microcirculation in preterm infants. Among survivors, LRM reduced the time to achieve the lowest FiO2 (60.0 versus 435.0 hours, p<0.0001), shortened respiratory support duration (25.0 versus 36.83 days, p = 0.044), and improved TcO2 index (1.00 versus 1.00, p = 0.009).